2011
DOI: 10.1021/ar1001445
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Properties of Superatom States of Hollow Molecules

Abstract: Electronic and optical properties of molecules and molecular solids are traditionally considered from the perspective of the frontier orbitals and their intermolecular interactions. How molecules condense into crystalline solids, however, is mainly attributed to the long-range polarization interaction. In this Account, we show that long-range polarization also introduces a distinctive set of diffuse molecular electronic states, which in quantum structures or solids can combine into nearly-free-electron (NFE) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(113 citation statements)
references
References 45 publications
2
111
0
Order By: Relevance
“…Because the IPS is a universal property of molecular sheets [56], the ILB is derived from IPS by stacking them into a 3D solid [57]; screening is inefficient, and similar hot electron dynamics could occur in other quasi-2D materials with low densities of states at the Fermi level. Moreover, thermionic emission can occur in other materials and is likely to be the dominant process for photoemission from plasmonic nanoparticles where hot electron generation and light localization are particularly efficient [91][92][93].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the IPS is a universal property of molecular sheets [56], the ILB is derived from IPS by stacking them into a 3D solid [57]; screening is inefficient, and similar hot electron dynamics could occur in other quasi-2D materials with low densities of states at the Fermi level. Moreover, thermionic emission can occur in other materials and is likely to be the dominant process for photoemission from plasmonic nanoparticles where hot electron generation and light localization are particularly efficient [91][92][93].…”
Section: Discussionmentioning
confidence: 99%
“…The ILB derives its 3D character from its physical origin in hybridization of IPSs of stacked graphene sheets, which give it characteristic probability density maxima in the interlayer space. Surprisingly, the ILB has never been reported in 2PP or optical spectroscopy of graphite; however, its existence is firmly established by theory as well as inverse photoemission and x-ray absorption spectroscopies [52][53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in contrast with empty fullerenes, 33 In the previous studies of Sc 3 N@C 80 (CF 3 ) 2 , we have found that the most stable structure has para-C 6 (CF 3 ) 2 hexagon on one pole (both CF 3 groups are bonded to PHHJs) and the Sc 3 N cluster located in such a way that one Sc atom is facing the cage hexagon on the opposite pole, whereas two other Sc atoms are coordinated close to the para-position of CF 3 -bearing carbon atoms. 35,36 Considering the idealized C 2 symmetry of this conformer (in the actual optimized structure C 2 symmetry is slightly distorted), we have studied 39 isomers of Sc 3 …”
mentioning
confidence: 99%
“…This clearly distinguishes the SAMO states from the higher lying Rydberg states. The unique nature of the potential was discussed in analogy with image potential states of graphene in the context of the STM experiments carried out by the Petek group [7]. For states with higher principal quantum numbers, the electron density is almost entirely outside the carbon cage and the electron-binding energies and properties more closely resemble those of conventional Rydberg series.…”
Section: Fullerene Super-atom Molecular Orbitals and Rydberg Statesmentioning
confidence: 99%